Self-Blame and PTSD Following Sexual Assault: A Longitudinal Analysis. Issue 5 (March 2021) - Kline, Nora K.; Berke, Danielle S.; Rhodes, Charla A.; Steenkamp, Maria M.; Litz, Brett T.
Sexual assault is a prevalent trauma associated with high rates of posttraumatic stress disorder (PTSD). Social cognitive theories posit that behavioral self-blame (i.e., attributing the cause of the assault to personal peri-event behavior) contributes to the etiology and maintenance of PTSD symptoms. Yet the direction of the association between self-blame and PTSD symptoms in the acute aftermath of sexual assault is unknown. This study evaluated temporal pathways between behavioral self-blame and PTSD symptom severity in an epidemiological sample of sexual assault survivors ( n = 126) assessed at four time points in the months immediately following the assault. Results of cross-lagged panel modeling revealed that reports of behavioral self-blame at the first assessment following sexual assault predicted PTSD symptom severity at Time 2. However, there was no association between behavioral self-blame at Time 2 and PTSD symptom severity at Time 3, nor was there an association between behavioral self-blame at Time 3 and PTSD symptom severity at Time 4. Instead, PTSD symptom severity predicted behavioral self-blame at Times 3 and 4. Findings suggest that behavioral self-blame following sexual assault may be particularly relevant to the onset of PTSD symptoms, while PTSD symptoms themselves appear to intensify subsequent perceptions of behavioral self-blame. Clinical implications and limitations are discussed.